Correlation Between Ne and Te Around 14:00 LT in the Topside Ionosphere Observed by CSES, Swarm and CHAMP Satellites - Yan, Rui; Xiong, Chao; Zhima, Zeren; Shen, Xuhui; Liu, Dapeng; Liu, Chao; Guan, Yibing; Zhu, Keying; Zheng, Lin; Lv, Fangxian (Frontiers in Earth Science, 2022)
In this study, we have performed a detailed analysis for the correlation between electron density (Ne) and temperature (Te) at the ionospheric topside altitude. In situ measurements from four satellite missions have been utilized, including the China Seismo-Electromagnetic Satellite (CSES), Swarm A and B, as well as the earlier Challenging Minisatellite Payload (CHAMP) satellite. To make a fair comparison, only simultaneous observations between CSES and Swarm A/B have been considered; while for CHAMP, as it doesn’t have overlaps with CSES period, only the observations during similar low solar activity years being considered. Our study has been confined to the dayside around 14:00 local time (LT), due to the fixed LT coverage of CSES. Observations from the four satellites show generally consistent relationship between the Ne and Te at the topside ionosphere. When Ne is low, the Te is negative correlated with Ne; however, the slop of negative relation becomes shallower or even reverses to a positive relation after Ne exceeds a certain threshold. The slope of Ne/Te relation shows also dependence on season and magnetic latitude (MLat), as the ionospheric Ne and Te themselves are seasonal and Mlat dependent. By considering the in situ measurements from four satellites at different latitudes, the relation between ionospheric topside Ne and Te seems to be dominated by the absolute value of Ne. Interestingly, we find two abnormal features of the Swarm Te measurements, that is when Ne is lower than 1×1011 m-3, Te sometimes becomes very scatter at low and middle latitudes; while when Ne is larger than 1×1011 m-3, Te are grouped into two branches at the equatorial and low latitudes. Further analysis reveals that the flags used in the Swarm Level-1 B plasma density product cannot well distinguish the two abnormal features of Te, implying further efforts are needed for the Swarm Te data calibration.